Management of distribution of course content, assignments and project for pre-service students using Moodle open source - Tamboli, Santosh Kumar (Voices of Teachers and Teacher Educators, 2015)
This article examines the use of Moodle, an open-source Learning Management System (LMS), for effectively managing the distribution of course content, assignments, and projects for pre-service students. As a flexible and widely adopted platform, Moodle offers a variety of tools that facilitate the organization and delivery of educational materials in a digital environment. The article highlights how Moodle's features, such as file sharing, discussion forums, quizzes, grading systems, and project management tools, can be leveraged to create a structured and interactive learning experience for pre-service students, particularly in teacher education programs. It explores the advantages of using Moodle to streamline administrative tasks, enhance student engagement, and support collaborative learning through peer assessments and group projects. Case studies and practical examples illustrate the implementation of Moodle in course design, tracking student progress, and ensuring timely feedback on assignments and projects. The article concludes by discussing the potential challenges and solutions in integrating Moodle into educational practices, emphasizing its role in promoting effective learning and teaching in modern educational settings.